Marijuana liberalization and public finance: A capital market perspective on the passage of medical use laws - CHENG, Stephanie F. (Institutional Knowledge at Singapore Management University, 2023)
We find that the staggered passage of state-level laws that legalize marijuana for medical use increases states' borrowing costs by 7–9 basis points. Consistent with economic theory on substance use suggesting that marijuana legalization increases local consumption of the drug (by expanding its availability and reducing its perceived risks), we predict and find that increased consumption represents an important mechanism that explains the higher state bond spreads. We also show that following such laws’ passage, states incur higher marijuana-consumption-related expenditures, including for police, corrections, and public welfare.